ANALISIS PENGARUH KUALITAS AUDIT, LEVERAGE, DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015--2017) - Albert Albert; Etty Widyastuti (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2019)
Earnings management is an important thing to that affects financial report as a base of decision making. This research aims to analyze the effect of audit quality, leverage, and managerial ownership on earnings management and how it affected the quality of financial report.This research use 267 data samples from manufacturing company listed in Indonesia Stock Exchange year 2015 – 2017. The methods of analysis use for the study are descriptive statistic method and multiple linear regression analysis method. The result of this research shows that audit quality has positive effect on earnings management, leverage has no effect on earning management, and managerial ownership has no effect onearnings management.